Inequities in Mortality and Potential Years of Life Lost (Pyll) in Greater Santiago, Chile, During and After the Covid-19 Pandemic - Vargas-Rona, C; Elorrieta-Lopez, F; Maddaleno-Herrera, M (BioMed Central Ltd, 2025)
Introduction: In Chile and worldwide, disparities in age-adjusted mortality rates and Potential Years of Life Lost (PYLL) intensified during the initial two years of the COVID-19 pandemic, with low- and middle-income countries experiencing a disproportionate burden. However, the post-pandemic landscape in Chile has yet to be comprehensively characterized. Objective: To evaluate the evolution of inequities in mortality rates and PYLL during the post-pandemic years (2022 and 2023) in Greater Santiago, comparing these with pandemic years (2020 and 2021) and the pre-pandemic period (2002–2019). Methods: This study uses publicly available data from the 34 urban municipalities of the Greater Santiago Metropolitan Region provided by the Department of Statistics and Health Information (DEIS) of the Chilean Ministry of Health. Inequality indices, such as the Concentration Index (CI) and the Relative Index of Inequality (RII), were estimated using the average per capita income of each municipality as the ranking variable. Results: Age-adjusted mortality rates and PYLL have re-established their pre-pandemic declining trajectory, although at different magnitudes. Concurrently, levels of inequity, although reduced from the peaks observed during the pandemic, have reverted to their prior upward trend. During the pandemic, between 2019 and 2020, mortality and PYLL increased by 31% and 32%, respectively, in the lowest-income municipalities, reaching levels comparable to those observed in 2002. In contrast, wealthier municipalities experienced substantially smaller impacts. These patterns were consistently observed across multiple inequality assessment methodologies, including municipal income quintile comparisons, the Concentration Index (CI), and the Relative Index of Inequality (RII). Conclusions: In Greater Santiago, although mortality rates and PYLL in 2023 declined below pre-pandemic levels, health inequities exhibited only a temporary decline. Subsequently, these disparities have resumed the upward trajectory characteristic of the pre-pandemic period. © The Author(s) 2025.